The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.taap.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenol cytotoxicity in kidney cells is associated with cytoskeleton disruption, autophagic vacuole accumulation, and mitochondrial dysfunction

Abstract: Water soluble fullerenes, such as the hydroxylated fullerene, fullerenol (C60OHx), are currently under development for diagnostic and therapeutic biomedical applications in the field of nanotechnology. These molecules have been shown to undergo urinary clearance, yet there is limited data available on their renal biocompatibility. Here we examine the biological responses of renal proximal tubule cells (LLC-PK1) exposed to fullerenol. Fullerenol was found to be cytotoxic in the millimolar range, with viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
120
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 57 publications
4
120
0
1
Order By: Relevance
“…Thus, the fullerene C 60 layers in our study were colonized with human osteoblast-like MG 63 cells to a similar extent as standard cell culture polystyrene dishes. We considered this result rather surprising, because many studies have reported cytotoxic and even genotoxic effects of fullerenes (Xu et al, 2009;Johnson-Lyles et al, 2010; for a review, see Bacakova et al, 2008a). However, the cytotoxic action of fullerenes was usually associated with suspending fullerenes in the cell culture medium (Yamawaki et al, 2006;Gelderman et al, 2008) or UV-light irradiation (Prylutska et al, 2010), while our fullerene layers were resistant to be dissolved in a water environment, and the cells were cultured in the dark.…”
Section: µM ----------mentioning
confidence: 91%
“…Thus, the fullerene C 60 layers in our study were colonized with human osteoblast-like MG 63 cells to a similar extent as standard cell culture polystyrene dishes. We considered this result rather surprising, because many studies have reported cytotoxic and even genotoxic effects of fullerenes (Xu et al, 2009;Johnson-Lyles et al, 2010; for a review, see Bacakova et al, 2008a). However, the cytotoxic action of fullerenes was usually associated with suspending fullerenes in the cell culture medium (Yamawaki et al, 2006;Gelderman et al, 2008) or UV-light irradiation (Prylutska et al, 2010), while our fullerene layers were resistant to be dissolved in a water environment, and the cells were cultured in the dark.…”
Section: µM ----------mentioning
confidence: 91%
“…81 It was elicited that lysosomal membrane permeabilization, lysosomal membrane rupture, and cytoskeleton disruption might be involved in lysosomal membrane destabilization, eventually resulting in autophagosome accumulation. 92 GO also leads to a decrease of p62, a protein that directly binds to LC3 and selectively incorporates into autophagosomes. 93 Moreover, p62 is preferentially degraded by autolysosomes; this degradation process is inversely correlated with autophagosomal maturation and degradation.…”
mentioning
confidence: 99%
“…In previous studies, it has been suggested that the relationship between mitochondria dysfunction and reactive oxygen species production could be the main pathway in causing nanotoxic effects in various cell lines via mitochondria dysfunction, linked with ATP production. [32][33][34][35][36] Based on these results, NPs might be capable of causing toxic effects induced by mitochondria dysfunction by interacting with proteins in ATP production, especially within electron transport, such as ATP synthase. In addition, NPs inside the vacuole or cell could induce cytotoxic effects through interactions with tubulin, such as disrupting cytoskeletons and causing cell death.…”
mentioning
confidence: 99%
“…Previously, fullerene was reported to cause cell death from cytoskeleton disruption and autophagic vacuole accumulation. 35 Regulation of actin polymerization or depolymerization was also involved with ZnO SM20(−) and ZnO SM20(+) . Commonly, tubulin and heat shock protein were also found to bind tightly to all types of ZnO NPs.…”
mentioning
confidence: 99%